Characteristics and control strategies for Diphtheria-Pertussis co-infection risk in the post COVID-19 era - Johnson, S.O.; Edogbanya , H.O.; Omolehin, J.O.; Johnson, O. (International Journal of Mathematical Analysis and Modelling, 2024)
Currently, the disruptions to routine vaccination programs induced during COVID-19 pan-demic have raised worries about possible resurgence of vaccine-preventable diseases like diphtheria and pertussis, particularly in infants and children with zero vaccination. This study aims to assess the risk of diphtheria-pertussis co-dynamics and control strategies in the post-pandemic era using modified SIR-type mathematical model. Our research is hinged on the premise that pathogens can coexist in a host and that diphtheria-pertussis are both preventable by (Diphtheria-Tetanus-Pertussis) DTAP vaccine. Therefore, the presented model captures epidemiological parameters and varying disease control coverage inputs to simulate disease behaviour in a population susceptible to both infections. Key non-optimal control parameters used are vaccination at birth, maternal derived immunity and partial quarantine for diphtheria only. The next generation matrix was used to derive the basic reproduction number R0 , after which stability analysis was conducted and it was observed that the formulated model exhibits four equilibrium points. The disease-free equilibrium and endemic equilibrium are shown to be locally and globally asymptotically stable. The forward sensitivity index was employed to pinpoint the effects of the hierarchy of parameters within R0. Furthermore, it was observed that the model would undergo backward bifurcation under certain conditions, Consequently, optimal control inputs should be considered for future research. Finally, theoretical accuracy of the diseases co-existence is validated via Numerical simulations and relevant graphical illustrations are displayed using MATLAB 2021a.